Industry diversity in entrepreneurial ecosystems: a longitudinal study of industrial composition and firm locations in Tel Aviv, Israel - Schäfer, Susann; Brenning, Alexander (Progress in economic geography, 2024)
This study contributes to understanding the evolution of entrepreneurial ecosystems by examining changes in industry composition and business locations within a specific ecosystem from its inception to 2020. Using longitudinal data from Tel Aviv-Jaffa, Israel, we investigate shifts in industries within the region and the location decisions of individual entrepreneurs within the city. By integrating these factors, we assess whether the ecosystem consists of distinct, industry-specific sub-ecosystems. Our findings highlight the significant role played by the 'social media and advertising' sector in shaping the ecosystem. Furthermore, we identify a trend of entrepreneurs clustering their businesses in a concentrated area within the city, suggesting enhanced communication and collaboration among entrepreneurs across different industries. However, we note an exception in the 'digital health and medical technologies' industry, where proximity to research institutions, multinational corporations, and hospitals holds greater significance than proximity to entrepreneurs from other sectors.